Simultaneous estimation of Aliskiren hemifumarate and Hydrochlorothiazide in combined Tablet Formulation by Simultaneous equation, Absorbance ratio and First derivative Spectroscopic Methods - Ashim Kumar Sen, Dhanya B Sen, Rajesh A Maheshwari, Ramachandran Balaraman, Avinash K Seth (Journal of Applied Pharmaceutical Science, 2016)
Three simple, sensitive, precise and accurate UV-spectroscopic methods namely simultaneous equation, absorbance ratio and first derivative (zero crossing) spectroscopic methods were developed and validated for simultaneous determination of aliskiren hemifumarate and hydrochlorothiazide in tablet dosage form. Simultaneous equation method was based on the measurement of absorbance at 271 and 280 nm for both the drugs. In absorbance ratio method 255 and 271 nm was used for the quantification of aliskiren hemifumarate and hydrochlorothiazide. First derivative method was involved in the conversion of UV-spectra in to first derivative spectra and measurement of first derivative signal at 241 and 280.2 nm for aliskiren hemifumarate and hydrochlorothiazide, respectively using 2 nm as wavelength interval (Δλ) and 1 as scaling factor. Methods were validated as per ICH guidelines including parameters viz., specificity, linearity and range, precision, accuracy, limit of detection and quantification. All the methods were found to be linear in the concentration range of 6-300 µg/ml for aliskiren hemifumarate and 0.5-25 µg/ml for hydrochlorothiazide. Results of validation studies follows ICH guideline acceptable limits. Methods were compared based on the assay results obtained using one-way ANOVA followed by Bonferroni multiple comparison tests (95% confidence level) as appropriate using computer based fitting program (Prism, Graphpad version 5, Graphpad Software Inc). Results of statistical analysis revealed that there was no significant difference between simultaneous equation, absorbance ratio and first derivative method. Developed methods were simple, rapid, highly sensitive and cost effective as compared to existing methods and can be useful for simultaneous estimation of aliskiren hemifumarate and hydrochlorothiazide in commercial tablet formulation for routine quality control.
Keywords: Aliskiren hemifumarate, hydrochlorothiazide, simultaneous equation, absorbance ratio, first derivative spectroscopic methods, tablet formulation.